Editorial: Operational AI - Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2024)
This editorial provides some reasoning behind the decision to publish the Special Issue section on “Perspectives on Machine Learning”. It also outlines the other content of this September issue and introduces the new Managing Editor of the Journal to take over in 2025.